Harnessing mesenchymal stromal cells for the engineering of human hematopoietic niches - Pievani, Alice; Savoldelli, Roberto; Poelchen, Juliane; Mattioli, Elisa; Anselmi, Giorgio; Girardot, Alice; Utikal, Jochen; Bourdely, Pierre; Serafini, Marta; Guermonprez, Pierre (Frontiers in immunology, 2021)
Tissue engineering opens multiple opportunities in regenerative medicine, drug testing and modelling of the hematopoiesis in health and disease. Recapitulating the organization of physiological microenvironments supporting leukocyte development is essential to model faithfully the development of immune cells. Hematopoietic organs are shaped by spatially organized niches defined by multiple cellular contributions. A shared feature of immune niches is the presence of mesenchymal stromal cells endowed with unique roles in organizing niche development, maintenance and function. Here, we review challenges and opportunities in harnessing stromal cells for the engineering of artificial immune niches and hematopoietic organoids recapitulating leukocyte ontogeny both in vitro and in vivo.
Gesehen am 29.07.2021